Physical activity used as punishment: advocating for better practices - Paulson, Lisa; Knipe, Robert (Journal of Physical Education, Recreation & Dance, 2023)
SHAPE America (2021) contends the use of physical activity used as punishment and/or behavior management as an inappropriate practice. The position statement acknowledges both the administration and withholding of physical activity as punishment, however, this paper focuses on the use of exercise as punishment (EAP) in physical education settings. While deemed inappropriate, the use of EAP is still happening today (Barney et al., 2016). The purpose of this viewpoint paper is to encourage appropriate pedagogies and practices while increasing awareness of national recommendations. Strategies for advocacy efforts are discussed.
Keywords: dept.hms; peer-reviewed

Secondary physical education teaching methods course: through the lens of the preservice teachers - Hodges, Michael; Phelps, Ashley; Knipe, Robert; Doherty, Brooke; Colburn, Jeff; Hamilton, Xiaofen D. (Curriculum Studies in Health and Physical Education, 2023)
Public school secondary physical education needs support. One approach in assisting is to improve the next generation of preservice physical education teachers (PPETs). The purpose of the study was to explore PPET secondary physical education training through the secondary teaching methods course offered in two universities in the US. A total of 14 PPETs participated in the study. Qualitative methods were employed through a phenomenological framework. Semi-structured interviews were analyzed using constant comparative methods [Kolb (2012). Grounded theory and the constant comparative method: Valid research strategies for educators. Journal of Emerging Trends in Educational Research and Policy Studies, 3(1), 83–86]. Two themes emerged: (a) PPETs have a stronghold on management, as they displayed feelings of high importance towards this topic, and (b) preparing for quality instruction when cooperating teachers are not, resulting in PPETs’ questioning the importance of lesson planning. PPETs views on the misalignment of university and district practices are troubling and suggest university and K-12 partnerships to be formed. Future research should examine ways to improve field experiences associated with these courses.
Keywords: Secondary teaching methods courses; college physical education students; curriculum and pedagogical knowledge; dept.hms; peer-reviewed; secondary physical education teacher preparation